The Influence of Digital Literacy and Adaptability on the Work Readiness of Generation Z Students in the Digital Era: A Case Study of FEBI Students at UIN North Sumatra - Tiara Devi Yanti Lestari; Marliyah Marliyah; Imsar Imsar (Fakultas Syariah IAIN Langsa, 2026)
The rapid advancement of digital transformation requires university graduates to possess not only academic competencies but also the ability to utilize technology effectively and adapt to the increasingly dynamic demands of the labor market. However, various studies indicate that technological proficiency among students is not always accompanied by adequate work readiness, resulting in challenges during the transition from higher education to professional employment. This study aims to analyze the influence of digital literacy and adaptability on the work readiness of Generation Z students at the Faculty of Islamic Economics and Business (FEBI), Universitas Islam Negeri Sumatera Utara. The research employed a quantitative approach with an explanatory associative design. A total of 98 students were selected as respondents using the Slovin formula from a population of 4,553 active students. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The findings reveal that digital literacy and adaptability have a positive and significant influence on work readiness, both partially and simultaneously. Adaptability demonstrates a more dominant influence than digital literacy. Simultaneously, both variables make a substantial contribution to shaping students’ readiness to enter the workforce. This study contributes to strengthening the understanding of the importance of integrating digital competencies and adaptive capacities as fundamental determinants of Generation Z students’ work readiness in the digital era.